Volume 2: Combustion and Fuels; Oil and Gas Applications; Cycle Innovations; Heat Transfer; Electric Power; Industrial and Coge 1993
DOI: 10.1115/93-gt-076
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Coolant Density on Film Cooling Effectiveness

Abstract: Experiments have been conducted on a large wind tunnel model of the leading edge region of a turbine blade. The model had a semi-circular leading edge in which four rows of holes were symmetrically placed about the stagnation line, two at ±15° and two at ±44°. Air and alternatively CO2 were injected from the coolant holes after contamination with a known small percentage of propane. Using a flame ionization detector and the mass transfer analogy, the film cooling effectiveness was measured at various overall m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The overall conclusion was that lm cooling provides better cooling effectiveness on the suction surface compared with that on the pressure surface. Several investigations (by Gartshore et al [8], Ou et al [9] and Mehendale et al [10]) have been made to resolve the effect of different parameters on lm-cooling effectiveness. It was observed that the lm-cooling effectiveness is a complex function of blowing ratio, density ratio, injection angle, blade geometry and the injection hole con guration.…”
Section: Relevant Literaturementioning
confidence: 99%
“…The overall conclusion was that lm cooling provides better cooling effectiveness on the suction surface compared with that on the pressure surface. Several investigations (by Gartshore et al [8], Ou et al [9] and Mehendale et al [10]) have been made to resolve the effect of different parameters on lm-cooling effectiveness. It was observed that the lm-cooling effectiveness is a complex function of blowing ratio, density ratio, injection angle, blade geometry and the injection hole con guration.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Mehendale and Han (1992) have shown that leading edge (or showerhead) film cooling can produce substantial levels of heat transfer augmentation, with increasing blowing ratio, even when high levels of inlet turbulence are present. Additionally, Gartshore (a al, 1993) in an experiment and Garg and Gaugler (1995) in a calculation have shown the heat flux in the showerhead region may not be uniform in either the spanwise or streamwise directions due to the joining of coolant jets from different rows leaving regions of good and poor coverage. In addition to showerhead configurations which typically have spanwise inclined holes, studies with spanwise and compound angle holes on flat plates such as Ligrani and Ramsey (1995), Sea, Schmidt, andBogard (1994), andEkkad, Zapata, andHan (1995) have also documented high levels of augmentation for turbulent boundary layers.…”
Section: Introductionmentioning
confidence: 99%